KONSEP MANUSIA IDEAL: TINJAUAN TEOLOGIS DAN PENDIDIKAN ISLAM - Nurti Budiyanti; Asep Abdul Aziz; Andewi Suhartini; Nurwadjah Ahmad; Ari Prayoga (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2020)
Learning is the process of fostering and developing the maximum human capacity that holds all dimensions of life, both regarding the soul, ideas, and heart that shape human character. But in reality, learning at this time still focuses on vocational aspects, on the contrary character is neglected, so that even the goals achieved have a partial character, not totality. It is fitting for the concept of learning to have a normative and integrative character, because there is a direction to be aimed in accordance with the thoughts of learning practitioners about the expected perfect qualifications of humans, which certainly link the spirit of the Koran in all aspects of life. Therefore, this research shares an overview of the involvement of all aspects of life in forming the concept of a perfect human being formed from the terms Bani Adam, Basyar, Insan, An-Naas, and 'Abdun.. The present study employed a qualitative approach in the form of literature study as a means of collecting data. Based on the study results and analyses, it was found that the ideal human concept established from the terms Bani Adam, Insan, An-Naas, Basyar and 'Abdun is a mention for humans viewed from various aspects, such as historical, psychological, sociological, biological, and theological aspects. In fact, these five aspects indeed indicate the perfection of humans as God's creatures. In particular, the ideal human being is a person who is aware of his status as a servant of Allah, aware of his role and function as khalifatullah, and also aware of his life's purpose to always makrifatullÄh. The educational implications of this concept cover goals, roles, functions, principles, educators, students, teaching contents, methods, and educational media. All of those implications must have a positive impact on the mind and heart as a means of increasing all the potentials possessed by humans. Thus, all the components of education are used as a means of strengthening faith, straightening worship, and instilling noble character and conduct towards makrifatullah.